2007
DOI: 10.1111/j.1471-4159.2007.05098.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity enhances aryl hydrocarbon receptor‐mediated gene expression and dioxin neurotoxicity in cortical neurons

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that belongs to the basic helix-loop-helix/ Per-Arnt-Sim transcription factor superfamily (reviewed by Rowlands and Gustafsson 1997;Hahn 1998 ] i , intracellular calcium concentration; AhR, aryl hydrocarbon receptor; ARNT, aryl hydrocarbon receptor nuclear translocator; BME, basal medium Eagles; CaMK, calcium/calmodulindependent protein kinase; CBP, cAMP-responsive-element binding protein; ChIP, chromatin immunoprecipitation; CYP1A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 51 publications
3
51
0
Order By: Relevance
“…As described for TCDD and other AhR ligands (NЈDiaye et al, 2006;Lin et al, 2008;Monteiro et al, 2008) (Monteiro et al, 2008). The exact mechanisms implicated in the phosphorylation of CaMKI␣ in response to AhR ligands remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…As described for TCDD and other AhR ligands (NЈDiaye et al, 2006;Lin et al, 2008;Monteiro et al, 2008) (Monteiro et al, 2008). The exact mechanisms implicated in the phosphorylation of CaMKI␣ in response to AhR ligands remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological and epidemiological studies revealed that exposure to environmental AhR ligands are associated with delayed development of brain sexual dimorphism, social behavior, learning ability, and neuropsychiatric disorders in both animal models and humans (Ikeda et al 2005;Nishijo et al 2007;Piedrafita et al 2008;Patandin et al 1999;Goetz et al 1994). Although AhR-mediated neurotoxicity has been demonstrated in various experimental systems (Kim and Yang 2005;Akahoshi et al 2006;Lin et al 2008), information were limited to its up-regulation of CYP1A1 and oxidative stress. The extent to which AhR participates in neuronal survival and plasticity remains poorly understood.…”
mentioning
confidence: 99%
“…Activation of AhR by these environmental toxins leads to cytotoxicity and carcinogenesis via induction of cytochrome P450 1A1/1A2 expression that generates toxic metabolites and induces oxidative stress (Nebert et al 2004). In mammalian brains, AhR is widely expressed in the cerebral cortex, hippocampus, hypothalamus, brainstem, and cerebellum (Petersen et al 2000;Powers et al 2005;Lin et al 2008). Information regarding the physiological roles of AhR in the brain is limited.…”
mentioning
confidence: 99%
“…Chromatin immunoprecipitation assay (Lin et al, 2008). Antibodies used for immunoprecipitation were mouse anti-GR (2 g; Abcam), mouse anti-HIF-1␣ (2 g; Novus), and rabbit anti-CREB (cAMP response element-binding) protein binding protein (CBP) (2 g; Santa Cruz Biotechnology) antibodies.…”
Section: Methodsmentioning
confidence: 99%